Pengembangan Media Video Edukasi untuk Mendukung Pemahaman Mahasiswa tentang Perilaku Kesehatan - Afriyanto, Dzul Fahmi; Kusumawati, Aditya; Indraswari, Ratih (FORIKES, 2025)
The limited availability of interactive learning resources in the Qualitative Health Behavior Study course makes it difficult for students to grasp concepts in depth. The purpose of this study was to develop and evaluate educational video media that is engaging, communicative, and tailored to student needs. The study employed Research and Development (R&D) methods, encompassing several stages: needs analysis, design, media development, expert validation, and small-scale and field trials. Validation results showed a feasibility rating of 90% from subject matter experts and 95% from media experts. Student trials yielded scores of 90% (small-scale) and 96% (field), categorized as